Personal Meaning Organization (PMO): A Hermeneutic Approach to Design - Sylleros, Álvaro; Taladriz, Begoña; Bernasconi, Renato; Pizarro, Francisco; Cádiz, Rodrigo F. (The Design journal, 2020)
Contemporary design exhibits a transition from the design of objects (as things) towards the design of interactions between subjects and objects (as processes). Furthermore, subjects are no longer considered users, but rather persons (personal identities). These persons perceive what we design from an autonomous self-referred meaning organization, which allows them to make embodied value judgments during the coupling process of interacting with material culture. Hence, for design research, it is essential to interpret these judgements as generative meanings capable of driving design decisions. Personal Meaning Organization (PMO) is a suitable framework to set out interpretative clues and a plausible explanatory model. It is based on early attachment processes understood as nuclear affective interactions that predetermine the organization of meanings within a coherent narrative structure. As we illustrate through a validation process, incorporating PMO into design is a convenient epistemological approach to solve the problem of creating interactions for others.